2013
DOI: 10.1007/s00299-013-1516-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of cut tree peony with glucose supply using the RNA-Seq technique

Abstract: Several unigenes encoding ACS and ERF involved in ethylene biosynthesis and signal transduction were greatly down-regulated in the petal transcriptome of cut tree peony 'Luoyang Hong' with glucose treatment. Glucose also repressed stress-related transcription factor genes DREB, CBF, NAC, WRKY and bHLH. Tree peony (Paeonia suffruticosa Andrews) is a famous traditional flower in China. Glucose supply prolonging vase life of cut tree peony flowers is associated with its role in the suppression of sensitivity to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 65 publications
3
26
0
Order By: Relevance
“…Of the 1,762,745 SNPs initially identified, only 77,174 SNPs were considered effective markers for use in the subsequent linkage analysis. These new markers constitute a more effective tool than currently used methods for genetic studies, such as genetic diversity assessment, genetic relationship analysis, and germplasm resource identification [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Of the 1,762,745 SNPs initially identified, only 77,174 SNPs were considered effective markers for use in the subsequent linkage analysis. These new markers constitute a more effective tool than currently used methods for genetic studies, such as genetic diversity assessment, genetic relationship analysis, and germplasm resource identification [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies reported the transcriptome sequencing of tree peony petals and flower buds. Zhang et al (2013) identified 50,829 unigenes with an average length of 585 bp. Zhou et al (2013) generated 59,275 and 63,962 unigenes with mean sizes of 698 and 699 bp from 2 types of tree peonies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the short reads generated by the Illumina platform can currently be assembled for a lower price, and a series of transcriptomes from non-model organisms have been successfully sequenced and assembled de novo (Li et al, 2012;Toledo-Silva et al, 2013). For tree peony, transcriptomes of petals and flower buds have been sequenced and millions of transcripts were obtained (Zhang et al, 2013;Zhou et al, 2013). Therefore, the Illumina platform is a preferable method for the transcriptome sequencing of peony leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic information of P. suffruticosa available to date includes three linkage maps (Cai et al, ; Guo et al, ; Zhang et al, ), 2,415 expressed sequence tags (ESTs) deposited to the NCBI database, and six RNA‐seq datasets. Although analysis of the expressed sequences had contributed a lot to our understanding of the mechanisms of flower bud development (Shu et al, ), reblooming (Zhou, Cheng, Wang, Zhong, & He, ), prolonging vase life of cut flowers (Zhang et al, ), and different color formation in petals (Zhang, Cheng, Ya, Xu, & Han, ) or leaves (Luo, Shi, Niu, & Zhang, ), our comprehensive and in‐depth understanding of the genetic basis underlying the numerous flower morphological differences, oil production, and medicinal use is still limited. The availability of a reference genome sequence of P. suffruticosa would be helpful for the integration of multi‐omics data across studies to enable more in‐depth research into the biology and genetics of tree peony.…”
Section: Introductionmentioning
confidence: 99%